THE INFLUENCE OF DIFFERENT ORGANIC HORMONES AFFECTS CHANGES IN THE NUTRITIONAL CONTENT OF Azolla Microphylla AS ANIMAL FEED - Naufal, Muhammad Agung; Meriksa Sembiring (Bajang Institute, 2024)
This research study aimed to determine changes in nutrition in Azolla sp. plants using several organic hormones and to determine the percentage of increased nutrient content in Azolla sp. plants. The experimental design used by the study was a non-factorial Complete Randomized Design (RAL), with 4 treatments and 5 repeats, The treatments tested are Z0 (without hormones, Z1 (banana weevil), Z2 (bean sprouts), and Z3 (sweet potato shoots). Hormones were tasted, taken from plants by adding EM4 bioactivators, and differentiated molasses for one week, except hormones from bean sprouts. The three fermentation results are complete and can be used as a planting medium for Azolla sp. The parameters observed were Changes in nutrition (crude protein, fat, and crude fiber in %) in Azolla sp. who are given some hormones from plants. The data obtained are tested by t-test. From the results of the research analysis that has been analyzed, it was found that the use of hormones derived from plants is very influential in increasing protein, increasing fat percentage, and reducing crude litter content in Azolla plants after being given various plant hormones. Of the three types of hormone origin, the best in increasing protein and fat and decreasing crude fiber was Z3>Z1>Z2 compared to Z0 treatment (control)